Time-dependent effects of calcium oxide on urban sludge dewatering in temporary lagoons and its application in sustainable urban development - Zhou, YunTian; Huang, Changfu; Wang, Yuan; Zhao, Xiaoming; Luan, Huanqiang; Zhang, Shuailong (Frontiers in Earth Science, 2025)
Calcium oxide (CaO) was used to condition urban sludge, with a focus on the impact of conditioning time, and its potential application in sustainable urban development was explored. In this study, the volume reduction ratio (VRR) was employed as the primary evaluation metric, and response surface methodology (RSM) was applied to investigate the combined effects of CaO dosage and conditioning time on sludge dewaterability. The optimal process conditions were determined, and the dewatering mechanism was analyzed. Results showed that the interaction between CaO dosage and conditioning time significantly influenced sludge dewatering performance. Under optimal conditions—0.48 g/g dry solids (DS) of CaO and 14.35 h of conditioning,the volume reduction ratio of sludge reached 72.76% ± 0.56%. Mechanistic analysis revealed that CaO conditioning promotes the embedding of calcium-based compounds into sludge flocs, forming a rigid skeletal structure that facilitates internal water release. These effects enhance with increasing conditioning time up to a certain threshold, thereby significantly improving sludge dewaterability. The findings highlight the potential of CaO conditioning as an effective strategy for sludge management in temporary lagoons and its broader implications for sustainable urban development.